Influence of electrode materials on molybdenum oxide/n-Si photodetectors. (7th November 2019) - Lin, Yi-Jou; Chen, Yi-Cin; Liu, Te-Hua; Lin, Chun-Chieh; Wang, Chih-Ming; Hsu, Yu-Kuei; Chen, Mei-Hsin; Lin, Chu-Hsuan
Abstract: Until recently, different metals have been adopted as the electrode materials for MoO x /Si photodetectors and solar cells, but the influence of these different metals has not been investigated. We have systematically studied and proved that the choice of metal has a great impact on optoelectronic performance. Ag and Al with similar low work functions display similar current–voltage behavior before and after the introduction of MoO x ; whereas Au and Ni which own similar high work functions lead to another type of current–voltage behavior. MoO x in the metal/MoO x /Si samples brings the superior diode behavior with an enhanced responsivity and decreased dark current as compared with the metal/Si samples. The choice of Ag as the top electrode on MoO x /Si has low alloying or defect formation with the MoO x /Si structure preventing the deterioration of the diode behavior, and the large downward band bending in MoO x at the Ag/MoO x junction facilitates the multitunnelling capture emission. This leads to high responsivity while maintaining the low dark current.